Acceptance and Introduction of Millet Dishes in Standalone Restaurants in Bangalore - Patil, Vachana R.; Palli, Nagarekha; Arjun, Priya (AMC Indian Journal of Entrepreneurship, 2019)
Millets are known as 'forgotten foods' and there is an urgent need to recognize millets as future super foods. Millets are some of the few cereal crops that can grow in arid lands, survive drought conditions, and are highly water efficient. People need to consume millets for a healthy lifestyle as they are packed with nutrients and have numerous benefits. The purpose of the study was to analyze the acceptance and introduction of millet dishes in stand-alone restaurants in Bangalore, which can be one of the benchmark sustainable practices in the hospitality sector. The objectives of the study was to examine menus of standalone millet serving restaurants, evaluating the awareness of millet products, consumption patterns of customers, and acceptability of popular millet dishes through explorative study. It also involved implementation of suggested menu which would help in the introduction of millets in non-millet serving restaurants. An explorative survey methodology was utilized, the primary tools of data collection were the questionnaire and discussions with the stakeholders. It was observed after the analysis that there was a big variance in the awareness and usage of millet products. Millet flavoured rice was the most popularly accepted dish amongst customers. Millets can be a promising alternative for wheat and rice. Promotion of millet dishes in restaurants will increase millet consumption. Increasing awareness amongst restaurant owners and consumers will lead to better acceptability of millet dishes on hotel menus and lead to sustainability of the crop and healthy lifestyle.